Impact of Body Weight on Blood Pressure Among University Students - Wahid, Nurmarni Athirah Abdul (Randwick International of Education and Linguistics Science Journal, 2024)
Body weight and blood pressure are two vital health indicators that are closely related. Excessive body weight or obesity, in particular, has been strongly associated with higher blood pressure, a key risk factor for cardiovascular diseases. Blood pressure, which measures the force of blood against the walls of blood vessels, is influenced by several factors, including body composition, physical activity, and diet. For young adults, maintaining a healthy weight is especially important, as early high blood pressure can result in long-term health issues. Recognizing the connection between body weight and blood pressure in this group is crucial for developing preventive measures against hypertension. This study examines the relationship between body weight and blood pressure among university students at the Universiti Teknologi MARA Pahang Branch Jengka Campus. A sample of 43 students, aged 18 to 22, from various faculties was selected for analysis. Descriptive statistics and Spearman rank correlation were used to investigate the association between body weight and blood pressure (systolic and diastolic). The results showed a statistically significant positive linear correlation, indicating that as body weight increases, both systolic and diastolic blood pressure also rise. These findings are consistent with previous research highlighting a strong linear correlation between body mass and blood pressure. The study underscores the importance of maintaining a healthy weight to reduce the risk of hypertension, particularly in young adults. Future research should explore additional factors affecting blood pressure and assess the effectiveness of weight management strategies in similar populations.